How can Neuro-Linguistic Programming Influence English Language Teaching? A Systematic Literature Review - Qushoy, Mohammad; Hartono, Rudi; Fitriati, Sri Wuli; Rukmini, Dwi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Integrating NLP into English language teaching transforms the classroom experience for educators and learners alike. Therefore, conducting a systematic review of current research is essential to identify gaps in the application of NLP within ELT. A review of the literature from 2010 to 2025 explores how Neuro-linguistic Programming (NLP) has been utilized to improve English Language Teaching (ELT), with particular attention to the types of NLP strategies applied, the specific language abilities addressed, the research methodologies employed, and the educational levels of the participants involved. Following the PRISMA model, 19 studies were selected from 590 retrieved across Scopus, ERIC, EBSCO, ScienceDirect, and ProQuest databases and analyzed using NVivo-14. The findings revealed that anchoring, reframing, and modeling were the most frequently applied NLP techniques in ELT, with reading comprehension being the most targeted language skill. Experimental research designs dominated the field, and university students were the primary participants studied. These results suggest that NLP techniques enhance learner engagement, motivation, and communication skills by creating dynamic and supportive learning environments. The study implies that educators and researchers can leverage NLP strategies to improve teaching effectiveness and learner outcomes in English language education. Further research is recommended to explore diverse participant groups and additional language skills to broaden NLP’s application in ELT contexts.